Utilization of offshore geothermal resources for power production - Baldur Kárason 1979- (2013)
Today geothermal energy has been utilized on land worldwide and the geothermal resources have a potential of being one of the greatest sustainable energy choices there is. Offshore geothermal energy has not been considered a feasible option, but with increasing energy prices and increasing knowledge of the utilization of this resource the choice becomes more attractive. The main objective for the project described in this thesis was to analyze and compare a number of configurations for potential power production from offshore geothermal resources. The options were analyzed mainly with technical feasibility in mind. A rough estimation of the economic aspects was performed as well. The energy output was calculated and compared for different energy processes using data from the geothermal field in Reykjanes Iceland. The goal of this work was to establish a map of available options and opportunities within the offshore geothermal industry with Reykjanes ridge particularly in mind. The main results indicate that technically it is possible to construct offshore power plants, but the main disadvantage is the high cost compared to a traditional power plants located on land. The most feasible option is a power plant located on land connected to a wellhead on the ocean bed. Thermoelectricity could be a favorable future power option but at this point the specific electricity production per size of the device is too small. Jarðvarmi hefur til dagsins í dag verið beislaður á landi um allan heim og hefur alla burði til að verða stærsti einstaki sjálfbæri orkugjafinn. Nýting jarðvarma á hafi hefur hingað til ekki verið talin fýsilegur kostur en með hækkandi orkuverði sem og vaxandi þekkingu á almennri jarðvarmanýtingu gæti þessi kostur reynst fýsilegri. Helsta markið þessa verkefnis var að greina og bera saman nokkra orkuferla sem allir hafa það sameiginlegt að nýta vökva úr jarðvarmaholu sem staðsett er á hafsbotninum utan Reykjanes. Ferlarnir voru aðalega greindir með tæknilega hagkvæmni í huga. Einnig var gerð gróf ...